2020
DOI: 10.5178/lebs.2020.72
|View full text |Cite
|
Sign up to set email alerts
|

The Evaluation of Second- and Third-Party Punishers

Abstract: Although punishment can promote cooperative behavior, the evolution of punishment requires benefi ts which override the cost. One possible source of the benefi t of punishing uncooperative behavior is obtaining a positive evaluation. This study compares evaluations of punishers and non-punishers. Two hundred and thirty-four undergraduate students participated in two studies. Study 1 revealed that, in the public goods game, punishers were not positively evaluated, while punishers were positively evaluated in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 12 publications
2
9
0
Order By: Relevance
“…Further, such evaluations were unaffected by whether the punisher had participated in the PG-P. These results are consistent with previous reports [30] , indicating that punishment may be considered undesirable as a means of maintaining group order. While laboratory experiments have shown that individuals will enforce punishment when it is the only form of sanction [8,35] , anthropological studies have found that punishment is not preferred in natural settings [38,39] .…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Further, such evaluations were unaffected by whether the punisher had participated in the PG-P. These results are consistent with previous reports [30] , indicating that punishment may be considered undesirable as a means of maintaining group order. While laboratory experiments have shown that individuals will enforce punishment when it is the only form of sanction [8,35] , anthropological studies have found that punishment is not preferred in natural settings [38,39] .…”
Section: Discussionsupporting
confidence: 91%
“…Speci cally, we focus on TPP with prisoner's dilemma game. Previous studies have shown a tendency for punishers to receive positive evaluations [30] . However, it is noteworthy that such literature usually employed a TPP with dictator game, where non-cooperative behavior is assumed to be solely generated by greed.…”
Section: Studymentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, observers might fear competitive punishers; therefore, they are not evaluated favorably. In contrast, cooperative punishers are regarded more favorably and receive a positive evaluation; they are more likely to be chosen as partners ( Mifune et al, 2020 ; Tateishi et al, 2021 ). It should be also noted that, in the present study, neither the punishers nor non-punishers received negative evaluations in Study 1 and 2, 7 especially when such punishment was the result of the punishers’ deliberation.…”
Section: Discussionmentioning
confidence: 99%